Steel fibre knitted fabric for automotive glass forming: Variations of the fabric thickness on the mould and glass optical quality. (March 2016) - Barburski, Marcin; Lomov, Stepan; Lanckmans, Filip; De Ridder, Frank
Extremely fine steel fibres (12 µm diameter) are spun into yarns and then knitted into fabric, which is used, among other applications, as a mould cover in the formation of automotive glass. High requirements of the glass quality (absence of dioptric distortions) ask for a perfect evenness of the mould cover surface, which depends on the local distortions of the fabric created during tensioning of the fabric over the mould. In this paper, compression behaviour of steel knitted fabrics combined with the fabric deformation in biaxial tension and shear is studied. Interaction of the fabric with the formed glass depends on the local changes of the fabric compression behaviour due to local fabric deformations on the mould. The deformation of the fabric is further linked to quality of the glass using quantitative optical distortion system based on moiré patterns to measure glass dioptric distortions.